Irreversible investment under Lévy uncertainty: An equation for the optimal boundary - Giorgio Ferrari; Paavo Salminen (Bielefeld University, Center for Mathematical Economics (IMW), 2014)
We derive a new equation for the optimal investment boundary of a general irreversible investment problem under exponential Lévy uncertainty. The problem is set as an infinite time-horizon, two-dimensional degenerate singular stochastic control problem. In line with the results recently obtained in a diffusive setting, we show that the optimal boundary is intimately linked to the unique optional solution of an appropriate Bank-El Karoui representation problem. Such a relation and the Wiener-Hopf factorization allow us to derive an integral equation for the optimal investment boundary. In case the underlying Lévy process hits any point in R with positive probability we show that the integral equation for the investment boundary is uniquely satisfied by the unique solution of another equation which is easier to handle. As a remarkable by-product we prove the continuity of the optimal investment boundary. The paper is concluded with explicit results for profit functions of (i) Cobb-Douglas type and (ii) CES type. In the first case the function is separable and in the second case non-separable.
Keywords: C02; E22; D92; G31; 330; free-boundary; irreversible investment; singular stochastic control; optimal stopping; Lévy process; Bank and El Karoui's representation theorem; base capacity